2012
DOI: 10.1111/j.1365-2702.2011.03939.x
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of the experiences of lesbian, gay and transgender parents accessing health services for their children

Abstract: Adopting a philosophy of family centred care can enable health providers and health professionals to provide lesbian, gay and transgender families with inclusive non-discriminatory care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 20 publications
1
91
0
16
Order By: Relevance
“…LGBT families-of-choice that are not related by blood or law are often unrecognized by providers, even though they provide consistent care, support, refuge, and nurturance to their members (Chapman et al, 2012). Although one in four LGBT older adults do have children (Fredriksen-Goldsen, Kim, et al, 2011) they are less likely to have children than their heterosexual peers (Fredriksen-Goldsen, Kim, Barkan, et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…LGBT families-of-choice that are not related by blood or law are often unrecognized by providers, even though they provide consistent care, support, refuge, and nurturance to their members (Chapman et al, 2012). Although one in four LGBT older adults do have children (Fredriksen-Goldsen, Kim, et al, 2011) they are less likely to have children than their heterosexual peers (Fredriksen-Goldsen, Kim, Barkan, et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that many lesbian, gay and bisexual (LGB) parents are unwilling to discuss their gender identity for fear of discrimination (Neville & Henrickson, ; Shields et al., ). This fear may cause them to avoid seeking healthcare for themselves and their children (Chapman, Wardrop, Freeman et al., ; Chapman, Wardrop, Zappia, Watkins, & Shields, ; Röndahl, ). In this paper, we intend to describe LGB parents’ experiences with child health care (CHC) nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Another area of LGB parents' rejection and discrimination are relations with health services. For example, lesbian mothers and gay fathers in Australia are still faced with prejudice and are forced to explain their personal situation and answer intrusive questions when seeking medical help for their children (Chapman et al, 2012). Also Ellen Perrin and Heidi Kulkin (1996) examined 255 non-heterosexual parents and have found, that 39% reported troublesome experiences in contact with primary pediatric care.…”
Section: Distal Stressorsmentioning
confidence: 97%